Insurgent memories: the parresia a dissident knowledge of the FARC-EP in times of transitional justice - García Gómez, Sebastián (2022)
The article intends in a schematic and exemplifying way, to carry out a study of the discourse that emerges in the context of the “Jurisdicción Especial para la paz (JEP)” in the framework of fulfillment with the final agreement for the termination of the armed conflict with the FARC guerrillas. It aims to show that transitional justice, at least in a formal way, is a mechanism that can put in tension the concepts of sovereignty, truth and power. In this sense and based on the studies of the French philosopher Michel Foucault, it is intended to discover a path that allows reinterpreting his studies about the phenomenon of parrhesia focused on a current experience, since this practice revolves, like transitional justice in an axis that juxtaposes the courage to say everything to the interpellation of sovereign power.